Predictive role of ABCD2, ABCD3I, C-reactive protein, neutrophil-lymphocyte ratio, platelet-lymphocyte ratio and systemic immune-inflammation index in 90-day and long-term stroke after transient ischemic attack - Kocatürk, İdris; Gülten, Sedat (The European Research Journal, 2023)
Objectives: Transient ischemic attack (TIA) is a neurological emergency and a precursor of ischemic stroke. ABCD2 and ABCD3I scores predict stroke after TIA, and clinicians use preclinical, clinical, and radiological parameters for calculating these scores. Our study aimed to investigate the efficacy of peripheral blood markers in predicting 90-day and long-term stroke risk after TIA. Methods: This retrospective study was conducted in Kastamonu Training and Research Hospital between January 2015 and November 2022. The demographic data of 99 patients who applied with the diagnosis of TIA and peripheral blood markers at the time of first admission to the hospital were used in the study. These parameters was evaluated in 90-day and long-term (>12 months) stroke after TIAs. Results: Of the 99 patients in our study, 59% (n = 58) were male. The mean age of the patients was 70 ± 13 years. ABCD2 (age, blood pressure, clinical features, duration of symptoms, and presence of diabetes mellitus) and ABCD3I (age, blood pressure, clinical features, duration of symptoms, presence of diabetes mellitus, dual TIA, and ipsilatheral carotis stenosis) scores and C-reactive protein (CRP) were statistically significant in predicting 90-day stroke. ABCD2 and ABCD3I were not effective in predicting long-term stroke. In addition, CRP, neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII) parameters were statistically significant in long-term stroke. CRP (AUC=793, sensitivity=82%, and specificity=81%) values were higher than ABCD2 (AUC=779, sensitivity=73%, and specificity=76%) and ABCD3I (AUC=755, sensitivity=82%, and specificity=70%) scores in predicting 90-day stroke. Conclusions: Our study showed that ABCD2, ABCD3I, and CRP effectively predict 90-day stroke after TIA. Furthermore, CRP was more effective than ABCD2 and ABCD3I scores in predicting 90-day stroke after TIA. CRP, NLR, PLR, and SII also effectively predicted long-term stroke after TIA.